Karate Sports Disciplines from the Spotlight of the Paradigm Shift of Japanese Combat Systems: Analytical Study - Anatoliy Lozovyy Anatoliy (Journal of Kinesiology and Exercise Sciences)
Background: Nowadays, many karate organizations hold their own competitions at various levels, up to and including the world championships. They are positioned as separate sports, although the content, rules and regulations of many of them differ only in details. A large number of similar sports versions of karate interfere with the correct understanding and objective assessment of karate in the modern world. Materials and Methods: Based on 40 years of practical experience in studying and teaching karate and on the results of his own research in 2019-2022, the author presents his point of view on the unification of sports versions of karate based on common systemic features into three separate sports. Like any sport, karate reflects the social phenomenon from which it originated. Using civilization-historical, functional and social approaches, the author suggests that the paradigm shifts in combat systems lead to the emergence of new forms that have deep systemic differences. Accordingly, these differences are also manifested in sports disciplines that have arisen on the basis of these forms. Results: Three forms of karate have a component with pronounced features of modern sport and form three systemically different competitive disciplines: 1) Style (Traditional) karate; 2) General karate; 3) Sports (Olympic) karate. The differences between them stem from the differences between the forms of karate from which they arose. Conclusions: Style, General and Sports karate are sports which require consideration in different paradigms. They are selfsufficient and equal in value and public demand.